The Future of Elementary Social Studies: Harnessing AI’s Potential Through Evidence-Based Practices - Grubaugh, Steven; Greg Levitt (Technium Social Sciences Journal, 2024)
This article explores the growing body of research evidence supporting the integration of Artificial Intelligence (AI) in elementary social studies education. It identifies and analyzes ten key evidence-based applications of AI that have demonstrated potential to enhance student engagement, personalize learning experiences, and cultivate essential historical thinking skills. The discussion critically evaluates the pedagogical implications, advantages, and challenges associated with AI integration in this context. Recommendations are provided for the responsible and effective implementation of AI tools in elementary social studies classrooms.